Ligand‐Shell Engineering of a Au28 Nanocluster Boosts Electrocatalytic CO2 Reduction. (28th June 2022) - Wang, Jie; Xu, Fan; Wang, Zhao‐Yang; Zang, Shuang‐Quan; Mak, Thomas C. W.
Abstract: Subtle tailoring of gold nanoclusters (NCs) could significantly change their physicochemical properties. However, direct comparison of the catalytic performance of gold NCs with identical metal cores but distinct ligand shells is rarely elucidated. In this work, a novel gold NC, Au28 (C2 B10 H11 S)12 (tht)4 Cl4 (Au28 ‐S ), was isolated by a facile self‐reducing synthesis. Au28 ‐S adopts an identical Au28 metal framework to that of the reported alkynyl‐protected Au28 ‐C . The different protective layers lead to distinctions in their electronic structure and optical properties. Furthermore, Au28 ‐S shows better catalytic activity for the electrochemical reduction of CO2 to CO. Theoretical calculations identified the active sites and shed light on the catalytic mechanism to elucidate the different catalytic performances. This work provides an ideal platform to study the protective layer‐activity relationship of gold NCs, and may also provide guidance in the design of metal NC‐based catalysts. Abstract : A carboranethiolate‐protected gold nanocluster Au28 ‐S was fabricated by a facile self‐reducing synthesis. Au28 ‐S has an identical metal core to the reported Au28 ‐C but different peripheral ligands. This ligand‐shell tailoring led to obvious differences in their electronic structures and optical properties. Compared to Au28 ‐C, Au28 ‐S shows superior catalytic activity and selectivity for the electrocatalytic CO2 reduction reaction.